2019
DOI: 10.1080/00268976.2019.1609706
|View full text |Cite
|
Sign up to set email alerts
|

Structural, elastic, electronic, andoptical properties of layered TiNX (X = F, Cl, Br, I) compounds: a density functional theory study

Abstract: Titanium nitride halides, TiNX (X = F, Cl, Br, I) in the α-phase (orthorhombic) are exciting quasi two-dimensional (2D) electronic systems exhibiting a fascinating series of electronic ground states under different conditions. Pristine TiNX are semiconductors with varying energy gaps and possess attractive properties for potential applications in the fields of optoelectronics, photovoltaics, and thermoelectrics. Alkali metal intercalated TiNCl becomes superconducting at reasonably high temperature in the α-pha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…It is instructive to note that the machinability indices of Ta X ( X = P, As) are comparable to widely mentioned MAX phase nanolaminates and other layered ternary and binary compounds including topological systems 5 – 7 , 125 130 . The high hardness of TaP is quite remarkable and exceeds that for many MAX phase compounds and related systems 120 , 125 – 134 . The high bond hardness of TaP found from bond hardness calculations supports the findings from the analysis of elastic constants and moduli of this WSM.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It is instructive to note that the machinability indices of Ta X ( X = P, As) are comparable to widely mentioned MAX phase nanolaminates and other layered ternary and binary compounds including topological systems 5 – 7 , 125 130 . The high hardness of TaP is quite remarkable and exceeds that for many MAX phase compounds and related systems 120 , 125 – 134 . The high bond hardness of TaP found from bond hardness calculations supports the findings from the analysis of elastic constants and moduli of this WSM.…”
Section: Discussionsupporting
confidence: 59%
“…TaP is significantly harder than TaAs but TaAs shows better machinability compared to TaP. It is instructive to note that the machinability indices of TaX (X = P, As) are comparable to widely mentioned MAX phase nanolaminates and other layered ternary and binary compounds including topological systems [5][6][7][125][126][127][128][129][130] . The high hardness of TaP is quite remarkable and exceeds that for many MAX phase compounds and related systems 120,[125][126][127][128][129][130][131][132][133][134] .…”
Section: Discussionmentioning
confidence: 90%
“…We have further calculated the Cauchy pressure, 𝐶 (= 𝐶 − 𝐶 ) that reflects the nature of bonding in a compound at the atomic level [51,52]. A material with positive Cauchy pressure is typically characterized to be a ductile material while the material's brittleness is represented by a negative value [53].…”
Section: Functionalmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23] Among many possible 2D materials, a new kind of system with a rectangular structure has been widely investigated due to its favorable physical properties including high carrier mobility, sensitive mechanical response, large optical absorption coefficient, and good catalytic and thermoelectric performance. [24][25][26][27][28][29][30][31][32][33][34][35][36] For example, Zhang et al predicted that the TiC monolayer has an indirect band gap of B0.2 eV and exhibits anisotropic electronic transport. 24 Zhou et al found that the band inversion in the ZrC monolayer can lead to the quantum spin Hall effect.…”
Section: Introductionmentioning
confidence: 99%